DOMINANT FEATURES OF PAINTING PORTRAITS IN VASYL BARKA’S NOVELS - Muzyka, T. Ye. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The article analyzes the dominant features of the portrait represented in the novels by Vasyl Barka «Yellow Prince. Volume II» and «Paradise». It finds that the portrait in the writer’s prose is based on the image of the character as a unity of physical, psychological and social aspects. It characterizes art techniques of the portrait such as mcroimages, symbols, artistic detail, landscape and interior, naturalistic descriptions, colors.